Wetlands construídos empregados para remoção de fósforo de esgoto sanitário - Nunes, Amanda Silva (2020)
The constructed wetlands have proven to be an attractive, sustainable and effective alternative for wastewater treatment, these systems are particularly efficient in removing carbon organic matter and nitrogen. However, they exhibit limited phosphorus removal rates. In this context, the objective of this study was to evaluate the phosphorus retention and removal dynamics in constructed wetlands (WCs) used in the treatment of raw sewage from an Effluent Treatment Plant. The study was carried out with the operation and monitoring of the French type WC system on a pilot scale, consisting of two stages of treatment sequence: one bed L1 (volume of 1 m³) of stage 1 in series with three beds L2, L3 and L4 (volume of 0.05 m³) of stage 2 operating in parallel. All beds were vegetated with Spathiphyllum wallisii. The system operated with an average flow of 0.48 m³. d-1 and distributed in 8 daily pulses of 0.06 m³ of 3 minutes each with a hydraulic rate of 272 mm.d-1 . The beds were filled with different materials, L1 was substantially composed of gravel, while the beds of the second stage L2, L3 and L4 were filled with sand, ceramic granulate and slag, respectively. The ceramic granulate and slag were used with the purpose of potentiating the phosphorus removal due to the high capacity of interaction with phosphorus. Between June/2020 and October/2020 weekly physical-chemical collections and analyses of the treated effluent and sewage generated were performed. The double stage vertical system presented a satisfactory general removal efficiency, but below the expected for similar systems. Stage 1 directly affected the overall efficiency of the system in most of the evaluated period, due to the increase of the average values of turbidity, TS and TSS, in relation to the affluent and low performance in relation to COD (23.28%), N-NH4 + (23.38%) and NTK (17.20%). Therefore, the second stage of the treatment was primordial to promote the treatment of sanitary sewage, ensuring in all cases an increase in the efficiency of the treatment in relation to the evaluated variables. The short time of operation and monitoring contributed especially on the effectiveness of the treatment in relation to the variables COD, N-NH4 + and NKT. As for the removal of Ptotal, the performance was quite significant, especially in L4, leading to the removal of 74.48%.The results confirm that the typical characteristics of the slag reflect in high rates of Ptotal removal. The results indicate that the main route of elimination of Ptotal was adsorption and precipitation along the oxides Fe, Ca and Al.